2006
DOI: 10.1242/jcs.03031
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Cdt1 induces chromosomal damage without rereplication and leads to chromosomal instability

Abstract: The activity of human Cdt1 is negatively regulated by multiple mechanisms. This suggests that Cdt1 deregulation may have a deleterious effect. Indeed, it has been suggested that overexpression of Cdt1 can induce rereplication in cancer cells and that rereplication activates Ataxia-telangiectasia-mutated (ATM) kinase and/or ATM- and Rad3-related (ATR) kinase-dependent checkpoint pathways. In this report, we highlight a new and interesting aspect of Cdt1 deregulation: data from several different systems all stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
140
1
18

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(169 citation statements)
references
References 63 publications
10
140
1
18
Order By: Relevance
“…S9). The G2 arrest indicates that wtCdt1 overexpression caused activation of the ATM DNA damage checkpoint pathways, as expected in the presence of functional p53 (32,37). The two mutants displayed a reduced ability to block cell-cycle progression and to induce such a checkpoint response (Fig.…”
Section: Cdt1 Residues Buried In the Cdt1-geminin Hexamer Are Importasupporting
confidence: 54%
See 1 more Smart Citation
“…S9). The G2 arrest indicates that wtCdt1 overexpression caused activation of the ATM DNA damage checkpoint pathways, as expected in the presence of functional p53 (32,37). The two mutants displayed a reduced ability to block cell-cycle progression and to induce such a checkpoint response (Fig.…”
Section: Cdt1 Residues Buried In the Cdt1-geminin Hexamer Are Importasupporting
confidence: 54%
“…In animal cells, overexpression of Cdt1 induces DNA re-replication (19,20,(32)(33)(34)(35), DNA fragmentation (36), chromosomal instability (37), and ATM/ATRdependent checkpoint activation (20,36). We therefore tested in U2OS cells wtCdt1 and the same two inactive mutants as in the Xenopus experiments for their ability to induce DNA rereplication, chromosomal damage, and checkpoint activation.…”
Section: Cdt1 Residues Buried In the Cdt1-geminin Hexamer Are Importamentioning
confidence: 99%
“…Overexpression of Cdt1 alone in many types of mammalian cells is sufficient to induce rereplication (17)(18)(19). Previous studies have broadly defined three functional domains of Cdt1: a domain in the middle of the molecule containing the major Geminin interaction site; an N-terminal domain, which is required for ubiquitin-mediated proteolysis and contains a second interaction site for Geminin; and a C-terminal domain, which is required for association with Mcm proteins (12).…”
mentioning
confidence: 99%
“…Recently accumulated evidences have strongly suggested that these mechanisms are mutually tight-coupled functions rather than they independently work. Molecular genetic studies have also provided supporting evidence for the idea that mutation in genes (HIRA/Tuple1, XCDT1, cdt1, Orc2, Orc3, Orc5, MCM2, MCM4, MCM10, RECQL4) (Maiorano et al 2000;Nishitani et al 2000;Pflumm and Botchan 2001;Christensen and Tye 2003;D'Antoni et al 2004;Prasanth et al 2004;Tatsumi et al 2006) required for www.intechopen.com Fundamental Aspects of DNA Replication 120 DNA replication or DNA repair (SCC2, SMC1, SMC3, ESCO2) (Gillespie and Hirano 2004;Bekker-Jensen et al 2006;Gandhi et al 2006;Yoshizawa-Sugata and Masai 2009) showed abnormal phenotype in chromosome structure, inherited diseases, genomic instability or prone to cancer, or aberrant replication timing causes abnormal chromosome condensation. Cytogenetical observation of chromosome is certainly a most direct approach for elucidates how dynamics of chromosome structure formation and chromosome recombination are coupled with DNA replication.…”
Section: Introductionmentioning
confidence: 95%